Разложите на множители:1. (a - x)(x[latex]^{3}[/latex] - [latex]y^{3}[/latex] - (x - y)(a[latex]^{3}[/latex] - x[latex]^{3}[/latex])2. a[latex]^{2}[/latex] - 25 - 2a(a[latex]^{2}[/latex] - 25) + a[latex]^{2}[/latex](a[latex]^{2...
Разложите на множители:
1. (a - x)(x[latex]^{3}[/latex] - [latex]y^{3}[/latex] - (x - y)(a[latex]^{3}[/latex] - x[latex]^{3}[/latex])
2. a[latex]^{2}[/latex] - 25 - 2a(a[latex]^{2}[/latex] - 25) + a[latex]^{2}[/latex](a[latex]^{2}[/latex] - 25)
3. n[latex]^{2}[/latex] +an[latex]^{3}[/latex] - n - a
4. b[latex]^{2}[/latex] -bc - a[latex]^{2}[/latex] + ac
Прошу помощи!
(немного накосячила с вводом квадрата и куба, но вроде понятно..)
Ответ(ы) на вопрос:
1.(a - x)(x -y^{3}) - (x - y)(a - x)=
(а-х)(х-у)(х2+ху+у2) - (х-у)(а-х)(а2+ах+х2)=
(а-х)(х-у)(х2+ху+у2-а2-ах-х2)=
(а-х)(х-у)(у2-а2+ху-ах)=(а-х)(х-у)((у-а)(у+а)+х(у-а))=(а-х)(х-у)(у-а)(у+а+х)
2. a - 25 - 2a(a - 25) + a(a - 25)=(а2-25)(1-2а+а2)=(а-5)(а+5)(1-а)^2
3. n3 +an2 - n - a=n2(n+a)-(n+a)=(n+a)(n2-1)=(n+a)(n-1)(n+1)
4. b -bc - a + ac = (b2-a2)-c(b-a) = (b-a)(b+a)-c(b-a)=(b-a)(b+a-c)
Не нашли ответ?
Похожие вопросы